Moving polewards in winter: a recent change in the migratory strategy of a pelagic seabird? - Quillfeldt, Petra; Masello, Juan F.; McGill, Rona A.R.; Adams, Mark; Furness, Robert W. (2021)
Background: During the non-breeding period, many birds migrate to milder areas, found closer to the equator than their breeding sites. Opposite movements are very rare. In the Southern Ocean, the abundance of 13C declines markedly with more southern latitude, providing a characteristic 13C isoscape. This can be used as a tracer for the movement of seabirds between breeding and inter-breeding areas, by comparing stable isotope ratios of feathers grown at different times of the year. Results: We studied seasonal movements of Thin-billed prions (Aves, Procellariiformes), breeding at the Subantarctic Falkland/Malvinas Islands, compared with those of Wilson's storm-petrels breeding in the Antarctic South Shetland Islands. The two species showed opposite migratory movements. While Wilson's storm-petrels moved to warmer waters north of the Drake Passage in winter, Thin-billed prions showed a reversed movement towards more polar waters. Carbon stable isotope ratios in recent and historical feathers indicated that poleward winter movements of Thin-billed prions were less common historically (45% in 1913-1915), and have only recently become dominant (92% in 2003-2005), apparently in response to warming sea temperatures. Conclusions: This study shows that pelagic seabirds can rapidly change migration strategies within populations, including migration towards more poleward waters in winter.